Law Schools and the Continuing Growth of the Legal Profesion - Kritzer, Herbert M. (Oñati Socio-Legal Series, 2013)
In most countries for which data are available, the size of the legal profession has continued to grow over the last 40 plus years. This continued growth reflects the perceived attractiveness of a career as a legal professional (i.e., the demand) and the incentives of the institutions that provide legal education, and hence serve as primary gatekeepers, to maintain or increase the number of students they enroll. In some countries, perhaps most prominently the United States, structural changes in the opportunities for careers in the legal profession are likely to put pressure on law schools that could result in changes in the supply of opportunities to obtain the legal education required to become a lawyer.